Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/lio2.240
|View full text |Cite
|
Sign up to set email alerts
|

The current practice of open neck mass biopsy in the diagnosis of head and neck cancer: A retrospective cohort study

Abstract: Objective To characterize current use of open neck mass biopsy for diagnosis of squamous cell carcinoma in patients presenting with a neck mass. Methods Using the University of Michigan Specialized Program of Research Excellence in Head and Neck Cancer patient database (2008–2014), we reviewed patients’ referral documentation to identify those who received open neck mass biopsies as part of their squamous cell carcinoma diagnosis. We compared subsequent treatment betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Several studies have demonstrated no impact on survival when excision biopsy is performed on a solitary neck node prior to radical radiotherapy. [25][26][27] Indeed, the combined 5-year overall survival in this series, including the oropharyngeal and unknown primary cases, was 87.5 per cent, comparing favourably with our published outcomes for all HPV positive and negative SCC (83 per cent and 53 per cent, respectively), 28 which is reassuring. However, we hope that optimisation of the investigation strategy will help improve our pre-open biopsy diagnostic rate and potentially help to reduce the overall pathway time by reducing uncertainty regarding investigations.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have demonstrated no impact on survival when excision biopsy is performed on a solitary neck node prior to radical radiotherapy. [25][26][27] Indeed, the combined 5-year overall survival in this series, including the oropharyngeal and unknown primary cases, was 87.5 per cent, comparing favourably with our published outcomes for all HPV positive and negative SCC (83 per cent and 53 per cent, respectively), 28 which is reassuring. However, we hope that optimisation of the investigation strategy will help improve our pre-open biopsy diagnostic rate and potentially help to reduce the overall pathway time by reducing uncertainty regarding investigations.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, US-guided CNB has been reported as an effective, inexpensive, time-efficient, safe, and minimally invasive diagnostic tool for neck nodal disease 11 , 12 . According to previous reports, the sensitivity, specificity, and accuracy of CNB for neck masses were about 99.7%, 100% and 99.46%, respectively 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This data collection is approved for studies involving anything from cesarean section complications to head and neck cancer diagnoses. 15,16 Due to the fact that the restrictions of the AP course did not make a randomized controlled trial feasible as a study type, not all statistics regarding the Cologuard test could be analyzed. Though it would have been preferable to conduct a statistical analysis with both sensitivity and specificity, determining specificity from secondary data collected in the past is not possible.…”
Section: Methodsmentioning
confidence: 99%